Climate change compounding risks in North Africa - Imed Drine (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The impact of climate change on agriculture and poor groups' livelihoods are one of the greatest potential threats to development and a key challenge in climate change agenda. The North Africa region is particularly vulnerable to climate change due to geographic and ecological features. The situation is aggravated by the interaction of multiple economic and social sources of stress and further compounded by low adaptive capacity. This paper describes the interaction between climate change, economic development, and social stability in the North African region. An empirical-statistical crop climate model is used to measure the possible impact of climate change on agriculture sector.
Keywords: Q54; Q56; 330; climate change; vulnerability; North Africa; economic development